2012
DOI: 10.1080/00986445.2012.660712
|View full text |Cite
|
Sign up to set email alerts
|

Developments on Wetting Effects in Microfluidic Slug Flow

Abstract: Wetting effects form a dimension of fluid dynamics that becomes predominant, precisely controllable and possibly useful at the micro-scale. Microfluidic multiphase flow patterns, including size, shape and velocity of fluidic particles, and mass and heat transfer rates are affected by wetting properties of microchannel walls and surface tensions forces between fluid phases. The novelty of this field, coupled to difficulties in experimental design and measurements, means that literature results are scarce and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 28 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…For example, with the same resazurin system, Yang et al [33] reported that the measured k L a was reduced along the channel length as τ = 1-5 s. This is because: (1) the large channel dimension (w = h = 2 mm) abated the intensity of internal circulation; (2) the reaction rate of oxygen with low resazurin concentration (0.1 g/L, corresponding C max = 0.199 × 10 -3 mol/L vs. C*=0.255 × 10 -3 mol/ L) might be smaller than its physical transport rate, especially when resazurin conversion approached 100%, leading to the presence of oxygen molecules at the interface or even in the slug bulk. In a recent work of the same group [34], the time-related k L a was also presented in an FEP circular tube (d = 1 mm, 0.1 g/L resazurin solution) under nonwetting slug flow (i.e., the liquid film was absent), which largely attenuated the internal mixing [51]. In comparison, the wetting slug flow within rectangular microchannel in the current work induced evident leakage flow and intensive internal circulation (will be explained in the following text), together with the low conversion of resazurin (mostly < 60%) allowed us to obtain the intrinsic k L a in the current residence time range.…”
Section: Mass Transfer In the Main Channelmentioning
confidence: 99%
“…For example, with the same resazurin system, Yang et al [33] reported that the measured k L a was reduced along the channel length as τ = 1-5 s. This is because: (1) the large channel dimension (w = h = 2 mm) abated the intensity of internal circulation; (2) the reaction rate of oxygen with low resazurin concentration (0.1 g/L, corresponding C max = 0.199 × 10 -3 mol/L vs. C*=0.255 × 10 -3 mol/ L) might be smaller than its physical transport rate, especially when resazurin conversion approached 100%, leading to the presence of oxygen molecules at the interface or even in the slug bulk. In a recent work of the same group [34], the time-related k L a was also presented in an FEP circular tube (d = 1 mm, 0.1 g/L resazurin solution) under nonwetting slug flow (i.e., the liquid film was absent), which largely attenuated the internal mixing [51]. In comparison, the wetting slug flow within rectangular microchannel in the current work induced evident leakage flow and intensive internal circulation (will be explained in the following text), together with the low conversion of resazurin (mostly < 60%) allowed us to obtain the intrinsic k L a in the current residence time range.…”
Section: Mass Transfer In the Main Channelmentioning
confidence: 99%
“…It was identified that, at a low Reynolds number (Re ≈ 60) airflow, drag force on water droplets is minimal, allowing droplets to grow until the channel is obstructed and subsequently be convected by airflow. Santos and Kawaji [43] investigated numerically wetting effects in microfluidic slug flow. They verified that the significant velocity slip developed in hydrophilic microchannels [44][45][46] is absent when the channel walls are hydrophobic, since gas slugs fill the channel cross section.…”
Section: Introductionmentioning
confidence: 99%
“…Many emerging studies have emphasized the interfacial wettability effects on multiphase transport processes. Specifically, interfacial wettability effects have been investigated in terms of fluid dynamics (drag reduction and wet particle collision), hydrodynamics (membrane bubbling and sieve tray), heat transfer and anti‐icing, oil recovery, oil–water separation, micro‐reactor technology, and so forth.…”
Section: Introductionmentioning
confidence: 99%